1976
DOI: 10.1080/0002889768507551
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of chloroform as determined by single and repeated exposure of laboratory animals

Abstract: The acute and chronic toxicity of chloroform has been studied in laboratory animals. An acute oral LD50 of 2.0 (1.0-3.8) g/kg was determined for male rats. When applied to the skin of rabbits, chloroform produced slight to moderate irritation and delayed healing of abraded sking. Absorption of chloroform through the skin of rabbits was apparent but absorption is not expected to present a practical acute hazard. Liquid chloroform produced slight injury to the eyes of rabbits which took over a week to heal. Repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 0 publications
0
10
0
4
Order By: Relevance
“…BDCM (but not CHCl3) has been demonstrated to be mutagenic (16). CHCl3 produces site-specific degeneration and necrosis of epithelial cells in the proximal tubules of rodent kidneys (17)(18)(19), although high doses may also induce damage in the distal nephron. BDCM administered by intragastric gavage at a dose of 10 mg/kg for 10 days did not induce any histopathologic changes in the kidneys of male F344 rats (10).…”
Section: Introductionmentioning
confidence: 99%
“…BDCM (but not CHCl3) has been demonstrated to be mutagenic (16). CHCl3 produces site-specific degeneration and necrosis of epithelial cells in the proximal tubules of rodent kidneys (17)(18)(19), although high doses may also induce damage in the distal nephron. BDCM administered by intragastric gavage at a dose of 10 mg/kg for 10 days did not induce any histopathologic changes in the kidneys of male F344 rats (10).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier work, Torkelson et al (1976) showed that chloroform vapor caused adverse effects in a variety of animals, including rats, rabbits, dogs, and guinea pigs. Metabolism of chloroform yields the trichloromethyl radical that forms the peroxyl radical 13 on reaction with oxygen; this reaction product can then serve as precursor to other ROS (Kovacic et al 2002 ).…”
Section: Chloroformmentioning
confidence: 98%
“…Leber und Niere waren gestaut und vergrößert (Tabelle 1; Chu et al 1980). Männlichen F344-Ratten wurden 15; 22,4; 30; 59,7; 89,5; 119,4 Chu et al 1980Torkelson et al 1976Lundberg et al 1986 Nach Schlundsondenapplikation von 34, 180 oder 477 mg Chloroform/kg KG an männliche F344-Ratten und von 34, 238 oder 477 mg Chloroform/kg KG an weibliche B6C3F 1 -Mäuse traten bereits nach einem Tag bei den Ratten der niedrigsten Dosisgruppe Nekrosen im proximalen Tubulus und verstreute zentrilobuläre Focibildung in der Leber auf. Ab 180 mg/kg KG war bei den Ratten der Labelling-Index erhöht und bei 477 mg/kg KG waren in der Niere ausgedehnte Nekrosen.…”
Section: Orale Aufnahmeunclassified
“…In (Torkelson et al 1976). Bei sechs Kaninchen traten nach Applikation von unverdünntem Chloroform schwere Hautirritationen auf (Duprat et al 1976).…”
Section: Orale Aufnahmeunclassified
See 1 more Smart Citation